2023
DOI: 10.1227/neu.0000000000002436
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Vestibular Schwannoma in Neurofibromatosis Type 2: An International Multicenter Case Series of Response and Malignant Transformation Risk

Abstract: BACKGROUND:Vestibular schwannomas (VSs) related to neurofibromatosis type 2 (NF2) are challenging tumors. The increasing use of stereotactic radiosurgery (SRS) necessitates further investigations of its role and safety.OBJECTIVE:To evaluate tumor control, freedom from additional treatment (FFAT), serviceable hearing preservation, and radiation-related risks of patients with NF2 after SRS for VS.METHODS:We performed a retrospective study of 267 patients with NF2 (328 VSs) who underwent single-session SRS at 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…We read with great interest the commentary provided by Hannan et al 1 regarding our article "Stereotactic Radiosurgery for Vestibular Schwannoma in Neurofibromatosis Type 2: An International Multicenter Case Series of Response and Malignant Transformation Risk." 2 We appreciate the opportunity to respond to the thoughtful comments of our esteemed colleagues from the United Kingdom.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the commentary provided by Hannan et al 1 regarding our article "Stereotactic Radiosurgery for Vestibular Schwannoma in Neurofibromatosis Type 2: An International Multicenter Case Series of Response and Malignant Transformation Risk." 2 We appreciate the opportunity to respond to the thoughtful comments of our esteemed colleagues from the United Kingdom.…”
mentioning
confidence: 99%
“…We affirm the necessity of stringent and meticulous criteria in evaluating the potential for RRM in patients with NF2, as highlighted in various studies. 1,12,13 Although the study cited by the authors reported an estimated 5% RRM risk, in some cases, identifying RRM hinged on the radiological observation of rapid tumor growth-a characteristic not uncommon in aggressive NF2 cases. 14,15 If tumors were indeed malignant, its swift growth would likely necessitate surgical resection and subsequent histological diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the recent publication by Bin-Alamer et al 1 which reported the results of a multi-institutional retrospective cohort study assessing the outcomes of stereotactic radiosurgery (SRS) NF2-schwannomatosis (NF2-SWN)–associated vestibular schwannomas (VS). The authors described the results of SRS treatment of 328 VS in 267 patients, with a median follow-up duration of 59 months.…”
mentioning
confidence: 99%
“…3 Given the minimally invasive nature of stereotactic radiosurgery (SRS) and its safety and efficacy in the management of VS, we sought to better understand the outcomes when VS SRS was performed in octogenarians. [3][4][5] In this study, we examined tumor control, need for additional tumor management and survival after SRS for VS in octogenarians.…”
mentioning
confidence: 99%